2021
DOI: 10.1021/acs.energyfuels.1c00809
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cleavage of the Diphenyl Ether C–O Bond over a Ni Catalyst Supported on AC with Different Pore Structures and Hydrophilicities

Abstract: Selective cleavage of C−O bonds in diphenyl ether (DPE), a lignin-derived 4-O-5 linkage, is a challenging topic and of great significance to produce value-added aromatic products for sustainable future. Activated carbon (AC) with different pore structures has different catalytic effects on the reaction. Herein, Ni catalysts supported on AC-1, AC-2, and AC-3 with specific surface area (SSA) values of 829, 1731, and 2399 m 2 /g, respectively, were investigated in the hydrogenolysis and hydrolysis of DPE. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…This phenomenon indicated that the activation time at 2.5 h was better than that at 2 h. The activation time was further increased to 3 h leading to an uneven distribution of pores in PAC-600-700-3 (Figure g). The longer activation time caused the enlargement of the pore size in Ni/PAC-600-700-3, which made a small part of Ni accumulate in the larger pores, resulting in an increase in the particle size . It was obvious that the particles of Ni were distributed on PACs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon indicated that the activation time at 2.5 h was better than that at 2 h. The activation time was further increased to 3 h leading to an uneven distribution of pores in PAC-600-700-3 (Figure g). The longer activation time caused the enlargement of the pore size in Ni/PAC-600-700-3, which made a small part of Ni accumulate in the larger pores, resulting in an increase in the particle size . It was obvious that the particles of Ni were distributed on PACs.…”
Section: Resultsmentioning
confidence: 99%
“…The longer activation time caused the enlargement of the pore size in Ni/PAC-600-700-3, which made a small part of Ni accumulate in the larger pores, resulting in an increase in the particle size. 40 It was obvious that the particles of Ni were distributed on PACs. Some Ni nanoparticles were difficult to find on Ni/PACs because SEM is just a surface technique.…”
Section: Catalyst Characterizationsmentioning
confidence: 99%
“…could effectively catalyse the hydrogenolysis of lignin model compounds and native lignin to aromatics. [18][19][20][21][22][23] Moreover, the catalytic activity of Ni-based catalysts could be improved when Ni is alloyed with other noble metals including Ru, Rh, Pd, or Au, where better performances toward aromatic products and stability were observed due to synergistic effects between Ni and the noble metals. 16,[24][25][26][27] Alternatively, recently, Wang, et al presented an excellent study on the hydrogenolysis of lignin using a carbon-modied Ni/MgAlO catalyst prepared by a carbothermal reduction method.…”
Section: Introductionmentioning
confidence: 99%
“…Common supports are mainly composed of HZSM-5, activated carbon, Al-SBA-15, carbon nanotubes, metal–organic framework, hydrotalcite, and Nb 2 O 5 . , The HDO reaction requires the active sites where hydrogenolysis, hydrogenation, and deoxidation are feasible as well as acid sites. ,, Generally, bifunctional catalysts containing Brønsted acid sites and Lewis metal sites such as HZSM-5, HY, and Hβ zeolites are regarded as promising catalysts. ,, The unitization of metal-impregnated zeolite in the HDO is widely explored due to its strong acidity, uniform pore size, and crystal structure, suggesting the high activity for the HDO. Additionally, compared with other oxide supports, high-surface-area zeolite supports are considered as the better choice for catalytic reactions because they allow higher dispersion of active metals and provide a higher contact area between the catalyst and the substrate. , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, compared with other oxide supports, high-surface-area zeolite supports are considered as the better choice for catalytic reactions because they allow higher dispersion of active metals and provide a higher contact area between the catalyst and the substrate. 26,27 Despite these efforts, the research on the HDO of lignin and its derivatives is still rare, especially in the cleavage of stable C−O bonds. Herein, the Ru/HZSM-5 catalyst prepared by an incipient wetness impregnation method was used in the HDO of diphenyl ether (DPE) and other lignin derivatives to explore the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%